BIPV: building envelope solutions in a multi-criteria approach. A method for assessing life-cycle costs in the early design phase. Issue 1 (2nd January 2017) - Bonomo, P.; Frontini, F.; De Berardinis, P.; Donsante, I.
ABSTRACT: The increasing demand for nearly zero energy buildings is rapidly contributing to changing the design criteria in architecture and concept of the building envelope. Today, photovoltaics (PV) is one of the most reliable technologies for integration in the built environment, and building-integrated photovoltaics (BIPV) is introducing a different notion of 'energy integrability' into practice. The difficulty of undertaking, from the first design stages, a really integrative approach towards energy (PV and building requirements) is today still one of the strongest barriers to the rise of the BIPV market. Likewise, the same uncertainty affects the economic aspects, objects of this paper, since BIPV systems are often evaluated similar to conventional installations. The typical consequence is to neglect their added value such as the multi-functionality of the system and therefore showing limited advantages of BIPV. Scope of this paper, starting from a multi-criteria approach, is to outline a new methodology for evaluating the cost-effectiveness of BIPV for the building skin. This method, based on a life-cycle costing approach and on the assessment of the whole building envelope solution, is expected to support architects during the early design phase in the research of the optimal design of BIPV, synergistically taking into account both PV and building quality. A comparison with conventional building elements and different PV technologies is also presented in order to strengthen the impact of the proposed methodology.